Traumatic Brain Injury—A Review of Intravenous Fluid Therapy - Pigott, Armi; Rudloff, Elke (Frontiers in Veterinary Science, 2021)
This manuscript will review intravenous fluid therapy in traumatic brain injury. Both human and animal literature will be included. Basic treatment recommendations will also be discussed.